Fluorescent Signaling of Molecularly Imprinted Nanogels Prepared via Postimprinting Modifications for Specific Protein Detection. Issue 4 (8th February 2021) - Tsutsumi, Katsuki; Sunayama, Hirobumi; Kitayama, Yukiya; Takano, Eri; Nakamachi, Yuji; Sasaki, Ryohei; Takeuchi, Toshifumi
Abstract : Previous reports have stated the advantages of postimprinting modification (PIM) to develop multifunctional molecularly imprinted polymers (MIPs). However, existing technologies have only been applied on bulk‐ and film‐based MIPs. Herein, the fluorescent signaling of nanogels (NGs) for protein detection is demonstrated. The NGs are prepared by molecular imprinting and PIM. A bivalent functional monomer, 4‐[2‐( N ‐methacrylamido)ethylaminomethyl] benzoic acid (FM1), comprising a benzoic acid moiety for interaction with proteins and secondary amine group for incorporating fluorescent reporter molecules is used. Human serum albumin (HSA), a marker protein for human health, serves as the model protein. HSA‐imprinted NGs (MIP‐NGs) are prepared by emulsifier‐free precipitation polymerization of FM1, N ‐isopropylacrylamide, 2‐methacryloxyethyl phosphorylcholine, and N, N′ ‐methylenebis acrylamide in the presence of HSA. After the removal of HSA, a fluorescent dye (ATTO 647 N) is treated with amino groups on FM1 residue as the PIM; this yields fluorescent‐signaling MIP‐NGs (FL‐MIP‐NGs) of ≈20 nm in diameter. The FL‐MIP‐NG‐based sensing system detects HSA in a real sample by selectively reading out the HSA‐binding events as high‐affinity fluorescence changes ( K d = 2.5 × 10 −9 M). The proposed MIP‐NGs functionalized via PIMs serve as advanced functional materials for sensing biorelated compounds. Abstract : Fluorescent‐signaling nanogels (NGs) (≈20 nm in diameter) for sensing human serum albumin (HSA) are prepared by molecular imprinting and postimprinting modification. The NG‐based sensing system selectively reads out the HSA‐binding events as high‐affinity fluorescence changes (apparent binding constant K d = 2.5 × 10 −9 M) and detects HSA in real samples.